Teak defoliator: changing host preference - may be climatic effect in Madhya Pradesh, India - Khan, Salman; Soni, Nikita; Yousuf, Mohd. (ENTOMON, 2017)
Hyblaea puera is a key defoliator pest of Tectona grandis commonly known as teak. Preliminary examination of teak shows that there is no attack or negligible attack on H. puera in Madhya Pradesh, India. But Vitex negundo which is a medicinal plant growing in the region which is moist enough have been attacked by these larvae. The larvae were collected from 150 plants and categorized in accordance with the no. of larvae collected. The change in host plant from Teak toÂ Vitex negundo is a phenomenon which involve climatic parameters and biological parameters.